2006
DOI: 10.1111/j.1525-1497.2006.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

An increase in religiousness/spirituality occurs after HIV diagnosis and predicts slower disease progression over 4 years in people with HIV

Abstract: There is an increase in spirituality/religiousness after HIV diagnosis, and this increase predicts slower disease progression; medical personnel should be aware of its potential importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
171
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(194 citation statements)
references
References 35 publications
10
171
0
13
Order By: Relevance
“…Evidências têm mostrado que as pessoas tornam-se ainda mais religiosas quando estão doentes, tanto física como mentalmente 25,26 . Em situações de alto estresse psicológico, a religião é frequentemente utilizada para auxiliar a lidar com situações de sofrimento ou a se adaptar a elas.…”
Section: Religiosidade E Pacientes Com Transtornos Mentais: Relações unclassified
“…Evidências têm mostrado que as pessoas tornam-se ainda mais religiosas quando estão doentes, tanto física como mentalmente 25,26 . Em situações de alto estresse psicológico, a religião é frequentemente utilizada para auxiliar a lidar com situações de sofrimento ou a se adaptar a elas.…”
Section: Religiosidade E Pacientes Com Transtornos Mentais: Relações unclassified
“…1 Thus, the authors conclude that the relationship between religiousness/spirituality and slower disease progression could not be accounted for by any of the above variables. 1 The authors acknowledge, however, that a limitation of their study is that the measure of religiousness/spirituality was a single item with 5 options which is unlikely to adequately capture the complexity of the concept. 1 This issue of what is meant by the word spirituality, as opposed to the term religiousness, continues to confound scientific study of this important dimension of human experience.…”
mentioning
confidence: 96%
“…1 The authors acknowledge, however, that a limitation of their study is that the measure of religiousness/spirituality was a single item with 5 options which is unlikely to adequately capture the complexity of the concept. 1 This issue of what is meant by the word spirituality, as opposed to the term religiousness, continues to confound scientific study of this important dimension of human experience. For example, in a qualitative study designed to explore in depth what patients understood by the word spirituality, McSherry et al 2 found that in general most were unclear about its meaning and considered it to be synonymous with religion.…”
mentioning
confidence: 99%
See 2 more Smart Citations